Symbol as an Orienting Means for Solving Developmental Tasks: A Personological Perspective - Belorusets A.S (Moscow State University of Psychology and Education, 2020)
The role of symbol in culture is in the focus of many works. In this paper, we aim to look at symbol from a personological perspective, that is, to consider it as a means of orientation in the tasks of personality development that is widely used in counseling and psychotherapy. Working with symbols is reflected in psychoanalysis, but it employs methods that are mostly based on interpreting symbols. These methods are founded on the understanding of symbol as a special semiotic unit: a sign with an unusual correlation between the signifier and the signified. Such interpretation is by all means possible and, in a way, productive, however, we would like to explore the model of working with symbol that is based on another understanding of its function. From our perspective, symbol is not the meaning of certain content, but its embodiment. The models of symbolic mediation of orienting activity that we are familiar with tend to describe the outcome of this process as a transition to the fixation of certainty in sign, that is, to the explanation of certain phenomenology. We, on the contrary, suppose that orienting activity, being a specially organised one and mediated by symbol, may result not so much in the fixation of certainty as in the emotional experience of belonging to the world, of comprehending the 'binding pattern', the feeling of 'presumption of solution' of life task. Such emotional experience/ attitude (as both intellectual and affective formation) turns out to be more reliable as a foundation for reconstructing one's life in the process of psychotherapy than pure thought containing an explanation.